2009
DOI: 10.1098/rspa.2009.0348
|View full text |Cite
|
Sign up to set email alerts
|

On the thermodynamic entropy of fatigue fracture

Abstract: Entropy production during the fatigue process can serve as a measure of degradation. We postulate that the thermodynamic entropy of metals undergoing repeated cyclic load reaching the point of fracture is a constant, independent of geometry, load and frequency. That is, the necessary and sufficient condition for the final fracture of a metal undergoing fatigue load corresponds to a constant irreversible entropy gain. To examine validity, we present the results of an extensive set of both experimental tests and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
227
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(238 citation statements)
references
References 26 publications
4
227
1
Order By: Relevance
“…The extension of their approach to electrical and chemical properties is also published in [30][31][32]. Naderi et al [33] also reported experimental results on the existence of a entropic limit at the time of the fatigue failure.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…The extension of their approach to electrical and chemical properties is also published in [30][31][32]. Naderi et al [33] also reported experimental results on the existence of a entropic limit at the time of the fatigue failure.…”
Section: Introductionmentioning
confidence: 79%
“…This hints of a possible existence of an information entropic limit to the acoustic entropy generated in the course of the fatigue failure of the materials. Previously, research by Naderi et al [33] showed that there exists a critical limit in the cumulative thermodynamic entropy generation (known as fatigue fracture entropy) beyond which fracture occurs. The evolutionary trend of the acoustic entropy, under various operating conditions tested in this study, also reveals a persistent trend over the course of the fatigue degradation.…”
Section: Entropy Of the Acoustic Responsementioning
confidence: 99%
“…[35] is normalized with respect to the FFE value for SS 304. These results have two important implications [35,37]: (a) fatigue damage accumulation is independent of load, frequency, and geometry; and (b) damage behavior under variable loading has no knee point and independent of multistage loading and loading sequence. As damage progresses towards the final fracture, the accumulated entropy monotonically increases to the fracture fatigue entropy (FFE) which is unique for a given material [37].…”
Section: Entropy In Fatigue Damage Processesmentioning
confidence: 99%
“…According to [35,37] entropy continuously increases simultaneously with the rise of degradation, towards the fatigue fracture entropy (FFE). Research shows that regardless of the type of the mechanical fatigue process (bending or torsion, tension-compression) FFE is constant unique to the material.…”
Section: Entropy In Fatigue Damage Processesmentioning
confidence: 99%
See 1 more Smart Citation